Prevalence of Hepatitis ’B’ in Apparently Suspected Individuals of Southern Punjab by Highly Sensitive Electro-chemiluminescence Immunoassay (ECLIA) - FAREED ZAFAR, ASGHAR JAVAID (Journal of Fatima Jinnah Medical University, 2018)
Background: The prevalence of hepatitis B virus (HBV) infection is increasing worldwide . This study was aimed to assess the prevalence of HBsAg among suspected patients for hepatitis by community doctors attending collection centers of Aga Khan University Hospital's clinical laboratory Karachi in Southern Punjab. Place and Duration: A retrospective study was conducted from January 2011 to June 2011 at Multan Stat Laboratory of Aga Khan University Hospital. Methods: A total of 2819 suspected patients were received at collection centers and included in this study. The screening was performed in Aga Khan Multan Stat Lab by using the Elecsys HBsAg 11 assay kit on Cobas e 411 immunoassay analyzer. Data was entered and analyzed using SPSS version 16 statistical package. Results: From the total of 2819 suspected hepatitis patients, 1809 (64.17%) were males and 1010 (35.83%) were females . HBsAg was found reactive in 623 (22.10%), borderline 10 (0.35%) and non-reactive in 2186 (77.55%) . Out of the total individuals, 475 (16.84%) male and 148 (5.25%) female were reactive for HBsAg. Sex-wise distribution of HBsAg reactive cases was 76.24% male & 23.76% female with M: F ratio of 3.2:1. The overall seroprevalence was found to be 22.10%. BAHAWALNAGER(55.84%), RAJAN PUR(JP) (52.30%), MUZAFARGARH (38.63%)and DERA GHAZI KHAN (34.87%) were most affected districts HBV infection. Conclusion: The overall prevalence of HBV is alarming high. Males were more affected. It is required to prevent the disease by giving education to the health personal as well as to general population.